Möglichkeiten der Einbeziehung von Vätern in der Eltern-Säuglings-Psychotherapie - Eickhorst, Andreas; Scholtes, Kerstin (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2011)
How to Involve Fathers in Parent-Infant Therapy - - This paper deals with the role of fathers within a context of parent-infant counseling or therapy. A review of the evidence regarding father-infant interaction and of fathers' involvement in therapeutic intervention is complemented by a case vignette of a young family. It illustrates the different personal characteristics of each parent in their family interaction and delineates options for therapists, notably the useful potentials of fathers.